Pengaruh Motivasi Ekstrinsik dan Disiplin Kerja Terhadap Prestasi Kerja Karyawan PT. XYZ - Ais Komala Sari; Ignatius Ario Sumbogo (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of extrinsic motivation and work discipline on employee performance at PT. XYZ. PT. XYZ is a company engaged in the distributor and importer of chemicals. There are three variables in this study which include extrinsic motivation, work discipline and work performance. This study uses quantitative methods by calculating the results of distributing questionnaires using paper questionnaires as its distribution to 30 respondents who are employees of PT. XYZ. The sampling technique in this study, using a saturated sample which is part of non-probability sampling and the research method used is multiple linear regression analysis using the SPSS 13 application.